Reducing tillage operations using combination disk plow and rotary blade on paddy soil - Amran, Faizal Amri; Ahmad, Desa (Universiti Putra Malaysia, 1999)
The investigating was initiated to explore the potential of combined operation of disk plow and rotary blade to reduce traveling of machine in the paddy soil that change relies on our ability to manage the effective of agricultural process at large scale. The work involved in the design a machine to anterior portion of prime mover. The design was evaluated under standard paddy field condition.